Understanding moral narratives as drivers of polarization about genetically engineered crops - Gabi Waldhof; Ulrich Fritsche (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2023)
Motivated by an increasing interest in narratives in economics, we investigated the relevance of moral concerns in narratives for policy preferences. Specifically, taking the German debate about genetic engineering of foods (GE) as an example, we conducted a representative online survey in Germany to identify common narratives, their moral content, and related subjective images about GE. In line with previous research, we found that two-thirds of respondents choose to reject GE. Moreover, based on Moral Foundations Theory, we found that GE opponents much more frequently addressed the moral foundations Care and Sanctity in their stated narratives about GE. GE supporters most frequently addressed the moral foundation Loyalty in their stated narratives about GE. Also, subjective images about GE were much more negative among opponents than among supporters. However, the subjective images of opponents and supporters were in striking accordance about GE being a deviation from what is considered normal. Both sides overwhelmingly described images related to the enhancement of plants, as something strange, supersized, or artificial. In a linear regression model, we showed that the moral content of narratives about GE is indeed significantly related to the attitude towards this technology. In total, the findings suggest that the moral content of narratives is highly relevant for policy preferences, and should thus be considered in science communication and policymaking.
Keywords: 330; narratives; Moral Foundations Theory; genetic engineering; morality; polarization